Flora and vegetation from the semiarid region of Acultzingo-Maltrata, Veracruz, Mexico - Rivera Hernández, Jaime Ernesto; Flores Hernández, Noé; Vargas Rueda, Abel Felipe; Alcántara Salinas, Graciela; Cházaro Basáñez, Miguel de Jesús; García Albarado, J. Cruz (Instituto de Ecología, A.C., 2018)
Background and Aims: In the central area of the state of Veracruz there is a semi-arid region, located mainly in the municipalities Acultzingo and Maltrata, within the Cañón del Río Blanco National Park. This region had remained unexplored from the botanical point of view and had therefore not been recorded by botanical literature. The aim of this research is to contribute to the knowledge of flora and vegetation of this region, through a floristic analisis and a description of its plant communities.Methods: Periodic collections of plants from August 2012 to July 2014 were undertaken. Additionally, the CORU and MEXU herbaria were reviewed, as well as the Flora of Veracruz series, to obtain historical records in the study area. In order to determine the taxa shared between this semiarid region and the Tehuacán-Cuicatlán Valley, a presence-absence matrix and a table summarizing the shared taxa were elaborated.Key results: Six hundred and four voucher specimens were collected, 45 records from CORU, 280 from MEXU and 80 from the review of the Flora of Veracruz series were obtained, resulting in a total of 1009 records. These data corresponded to 87 families, 247 genera and 390 taxa. The best-represented families are Asteraceae, Fabaceae, Apocynaceae, Cactaceae, Asparagaceae, Boraginaceae, Bromeliaceae, Orchidaceae and Verbenaceae. Thirty-three species were considered as new records for the state of Veracruz and 43 have a threat status in terms of national and international laws. Three different vegetal associations conforming the xerophytic scrub are extensively described.Conclusions: There are 63 species shared between the study area and the Tehuacán-Cuicatlán valley, thereby confirming the floristic relationships between these two large semi-arid regions; hence, we propose the name “Acultzingo-Tehuacán-Cuicatlán Valley”, covering the states of Veracruz, Puebla and Oaxaca.